Analysis of the prophages carried by human infecting isolates provides new insight into the evolution of Group B Streptococcus species. (May 2018) - van der Mee-Marquet, N.; Diene, S.M.; Barbera, L.; Courtier-Martinez, L.; Lafont, L.; Ouachée, A.; Valentin, A.-S.; Santos, S. Dos; Quentin, R.; François, P.
Abstract: Objectives: Group B Streptococcus (GBS) emerged in the 1970s as a major cause of neonatal infections, and has been increasingly associated with infections in adults since the 1990s. Prophages have been suspected to have driven these epidemiological trends. We have characterized the prophages harboured by 275 human GBS isolates belonging to the major lineages. Methods: We applied whole genome sequencing (WGS) to 14 isolates representative of the diversity within GBS species, located and identified their prophages. Using prediction tools, we searched for prophage elements potentially involved with the ability of GBS to infect humans. Using the data obtained by WGS, we designed a PCR-based tool and studied the prophage content of 275 isolates. Results: WGS of the 14 isolates revealed 22 prophages (i) distributed into six groups (A-F), (ii) similar to phages and prophages from GBS and non-GBS streptococci recovered from livestock, and (iii) carrying genes encoding factors previously associated with host adaptation and virulence. PCR-based detection of prophages revealed the presence of at least one prophage in 72.4% of the 275 isolates and a significant association between neonatal infecting isolates and prophages C, and between adult infecting isolates and prophages A. Conclusions: Our results suggest that prophages (possibly animal-associated) have conditioned bacterial adaptation and ability to cause infections in neonates and adults, and support a role of lysogeny with the emergence of GBS as a pathogen in human.